Effects of stockholders' secondary tax liability on corporate investment - Jangwook Lee (KDI Journal of Economic Policy, 2024)
This study analyzes the impact of secondary tax liability borne by stockholders, an exception to the principle of limited liability, on corporate investment. The paper constructs a model of a firm to examine the effect of this secondary tax liability, finding that the violation of limited liability increases firms' expected bankruptcy costs, thereby reducing investments. By means of an empirical analysis, the paper examines whether firms with the largest shareholder stake exceeding 50%, the condition under which secondary tax liability is incurred, decrease their investments. The results show that firm investment is highly concentrated in observations of cases in which the largest shareholder stake does not exceed 50%. Investments decrease sharply in cases where the largest shareholder stake exceeds 50%. The results here provide implications pertaining to how exceptions of the limited liability principle, existing only in Korea, affect corporate investments.
Keywords: G30; G38; 330; Secondary Tax Liability; Principle of Limited Liability; Corporate Investment